2013
DOI: 10.1177/0954008313483152
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of poly(arylene ether ketone) copolymers with pendant carboxylic acid groups for antifouling ultrafiltration membrane

Abstract: This work focused on the synthesis of a series of poly(arylene ether ketone) random copolymers with various controlled pendant carboxylic acid groups (PEAK-COOH) by direct copolymerization method and the preparation of antifouling ultrafiltration membranes via the conventional immersion precipitation phase inversion method. The morphologies of the PEAK-COOH membranes were investigated by scanning electron microscopy. In addition, the surface hydrophilicity and charged property of the PEAK-COOH membranes were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…where η is the water viscosity (8.9 × 10 −4 Pa s), Q is the volume of permeate pure water per unit time (m 3 /s), and Δ P is the operation pressure (0.1 MPa).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…where η is the water viscosity (8.9 × 10 −4 Pa s), Q is the volume of permeate pure water per unit time (m 3 /s), and Δ P is the operation pressure (0.1 MPa).…”
Section: Methodsmentioning
confidence: 99%
“…Membrane-based separation technologies, such as ultrafiltration (UF) and nanofiltration (NF), are efficient and environmental-friendly strategies for wastewater treatment and seawater desalination. [1][2][3][4] Among the available separation membranes, UF membrane, with a pore size of 1-100 nm, is the most widely used one to remove protein, colloid, bacteria, and humic substances, based on size-sieving mechanism. 5 The performance of UF membrane is generally determined by its water permeability, stain resistance, and reusability.…”
Section: Introductionmentioning
confidence: 99%
“…Carboxylated polysulfone-based FO membranes showed significant higher fluxes than PSF-based FO membranes [19]. Wang et al have found that the introduction of pendent carboxylic acid group into poly(arylene ether ketone) copolymers could prepare good antifouling ultrafiltration membranes [20]. We can conclude form the above that the carboxylated materials not only possess good solubility and high hydrophilicity, but also have anti-swelling property and dimension stability, when compared with other hydrophilic materials, such as sulfonated polymers which are difficult to be dissolved in solvent and susceptible to swelling in water at high sulfonation degree [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature, four different modification strategies have been proposed, 5,6 including (a) blending of the membrane material with modifying additives in casting solutions during membrane preparation (additive), 7,8 (b) advanced surface modification or functionalization after membrane preparation (post-modification), 9,10 (c) direct modification of the membrane material before membrane preparation (premodification), 11 and (d) synthesis of novel polymers with well-defined structures as membrane materials (synthesis). 12,13 In the additive method, the modification of the membrane is done through a simple blending technique, and no additional step is required during the membrane preparation process. However, the presence of the modifying additives in the membrane matrix leads to instability due to the migration and agglomeration phenomena, which could render a persistent antifouling property.…”
Section: Introductionmentioning
confidence: 99%